(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
PMDG is an Islamic boarding school that has several activities that require large amounts of electricity and students as staff who manage electricity or are electrical and diesel operators. Electric and diesel operators at PMDG are young students and do not yet know the dangers of electricity. Apart from that, they also work without using PPE. It can cause work accidents and other major impacts such as explosions and fires. This service aims to identify, assess, and analyze risks using the HIRA method, provide knowledge about electrical safety, as well as provide PPE and how to use it. The methods used are pretest, education, posttest, and mentoring. Based on the results of the activities, it was found that four electrical activities had a high risk: installation of switches, installation of new electricity, installation of new MCBs at height and connection, and cleaning of generator handles with PLN voltage. There was an increase in participants’ knowledge of 15.7%, increased skills in using PPE, and all participants were active. There needs to be continuity by providing intensive supervision and assistance regarding the implementation of electrical safety. Participants also need to be given training in dealing with work accidents caused by electricity. Keywords: electrical safety, education, operator, Islamic boarding school